2008
DOI: 10.1007/s10071-008-0203-y
|View full text |Cite
|
Sign up to set email alerts
|

Prairie dog alarm calls encode labels about predator colors

Abstract: Some animals have the cognitive capacity to differentiate between different species of predators and generate different alarm calls in response. However, the presence of any addition information that might be encoded into alarm calls has been largely unexplored. In the present study, three similar-sized human females walked through a Gunnison's prairie dog (Cynomys gunnisoni) colony wearing each of three different-colored shirts: blue, green, and yellow. We recorded the alarm calls and used discriminant functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
40
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(43 citation statements)
references
References 23 publications
2
40
0
1
Order By: Relevance
“…can be sufficient to start a brawl at a bar. Besides, bees communicate 'about' food [85], many animals use calls that refer to different predators [86,87] and grey parrots can learn to use sounds to refer to objects [44]. Some great apes can also learn to use signs or sounds to refer to objects [88,89].…”
Section: Deconstructing Language Into Biologically Tractable Unitsmentioning
confidence: 99%
“…can be sufficient to start a brawl at a bar. Besides, bees communicate 'about' food [85], many animals use calls that refer to different predators [86,87] and grey parrots can learn to use sounds to refer to objects [44]. Some great apes can also learn to use signs or sounds to refer to objects [88,89].…”
Section: Deconstructing Language Into Biologically Tractable Unitsmentioning
confidence: 99%
“…For species with multiple alarm call types, different call types may be used to communicate about different types of predators [42,43,45], to communicate different degrees of risk or response urgency [46,48], or to communicate both predator type and urgency [44,72]. Species living in more complex social groups, such as groups with more social demographic roles, may have greater need to signal alarm in a more complex manner and thus may use larger alarm call repertoires.…”
Section: Demographic Complexity Drives Repertoire Size Evolutionmentioning
confidence: 99%
“…Moreover, as it is typically the case that not all humans pose the same risk to prey species, distinguishing between different human subgroups to identify those associated with genuinely threatening situations could present a major cognitive challenge. The extent of behavioral flexibility that different species may exhibit in correctly classifying human predators-and the degree of sophistication possible in such abilities-is therefore of considerable interest.Most research on the abilities of animals to classify human predators has focused on discrimination through facial features or general differences in behavior and appearance (5,(11)(12)(13). This focus has demonstrated that a number of different species are able to use visual cues to distinguish between individual humans that present varying levels of threat (4, 5, 14-16).…”
mentioning
confidence: 99%
“…Most research on the abilities of animals to classify human predators has focused on discrimination through facial features or general differences in behavior and appearance (5,(11)(12)(13). This focus has demonstrated that a number of different species are able to use visual cues to distinguish between individual humans that present varying levels of threat (4, 5, 14-16).…”
mentioning
confidence: 99%